Experimental and numerical investigation into the behaviour of face-to-face built-up cold-formed steel channel sections under compression - Roy, Krishanu; Mohammadjani, Chia; Lim, James B.P. (Thin-walled structures, 2019)
Face-to-face built-up cold-formed steel channel sections are becoming increasingly popular for column members in cold-formed steel structures; its applications include cold-formed steel trusses, space frames and portal frames. In such an arrangement, the independent buckling of the members is resisted by intermediate fasteners. In the literature, no research is available for such face-to-face built-up cold-formed steel columns. The issue is addressed herein. This paper presents the results of 36 experimental tests, conducted on face-to-face built-up cold-formed steel channel-sections covering a wide range of slenderness from stub to slender columns. A nonlinear finite element model is then described that shows good agreement with the experimental results. The finite element model includes material non-linearity, initial imperfections and modelling of intermediate fasteners. Both finite element and experimental results are compared against the design strengths calculated in accordance with the American Iron and Steel Institute (AISI), Australian and New Zealand Standards (AS/NZS) and Eurocode (EN 1993-1-3). The verified finite element model is used for the purposes of a parametric study comprising 90 models. The effect of fastener spacing on the axial strength was investigated. From the results of experiments and finite element investigations, it is shown that the design in accordance with the AISI & AS/NZS and Eurocode (EN 1993-1-3) is generally conservative by around 15%, however, AISI & AS/NZS and Eurocode (EN 1993-1-3) can be un-conservative by 8% on average for face-to-face built-up columns failed through local buckling. •Experimental tests were conducted on face-to-face built-up CFS channel-sections.•Initial geometric imperfections were measured for all test specimens using a laser scanner.•Nonlinear finite element models were developed which includes material nonlinearity and initial imperfections.•The column strengths were compared against the design strengths calculated in accordance with AISI & AS/NZS and EN 1993-1-3.•The AISI & AS/NZS and EN 1993-1-3 design strengths are generally conservative by around 15% but un-conservative by 8% on average for columns failed through local buckling.